Eksperimen Tipografi dalam Visual untuk Anak - Setiautami, Dria (Bina Nusantara University, 2011)
Typography is one of the elements design, which can make children learn it as an image or as text. Article explores the impacts of typography for childrens. For children’s interest we have to make the experiment visual with a big fun expression. The fact is the shape of typography can’t be changed, that’s why we have to know how to change them and get another expression to another form. With the fun experimental typography we can make one of edutainment kit books for the children.